Needs Analysis English For Specific Purposes (ESP) For Vocational Pharmacy Students - Abd. Syakur; H.M Zainuddin; M. Afif Hasan (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2020)
Increased creation of academic programmes in vocational education programs, which is expected to be a solution for increasing Indonesia's human capital. This also underpins Indonesia's efforts to develop English language proficiency, as illustrated in Minister of Education and Culture. The Ministry of Education and Culture helped English vocational education students who required assistance with listening, reading, writing, and speaking improve their communicative skills. This study examines the needs of English courses (ESP) for educational students who need target and learning needs review. Questionnaires and interviews were used to collect data. The effects of data research on active communication skills (35%), grammar difficulties (25%), reading ability (25%), material difficulty (10 %), ability (25 %) and writing ( 5%). Basic pharmacy (20%), prescription pharmacy (20%), health and medications (20%), healthy lifestyle (20%), and microbiology and pharmacy (20%) are the topics covered (20 percent ). English Media (40%) is the most commonly used English language in technology, followed by crosswords (20%), dialogue content (20%), and multiple choice (20%). The study's findings are an overview of the needs and goals associated with the English learning process. The findings of a study of students' academic needs and their progress in learning English, including reading, writing, grammar, and other skills, in order to better prepare them to meet their future needs.